Load-deflection response of prestressed concrete beams strengthened with FRP: a comprehensive perspective - Kramer, Kimberly Waggle (Kansas State University, 2020)
Currently, degradation of pretensioned prestressed reinforced concrete (PRC) bridge structures is a serious problem in the United States of America. Since 2000, the use of fiber-reinforced polymer (FRP) is well studied and has become an accepted method to rehabilitate concrete bridges. Design engineers use the ACI 440.2R-17 to determine strength requirements. Additionally, evaluating the deflection of strengthened PRC members is required during the restoration/strengthening design. ACI 440.2R-17 relies on ACI 318-19 for deflection calculations and limits prestressing from yielding under service load levels. This dissertation examines the application of the effective moment of inertia equation given in ACI 318-19 for the determination of deflection after cracking of PRC beams externally strengthened with carbon fiber reinforced polymers (CFRP). The results reported in this dissertation deal with the behavior of partially prestressed concrete beams strengthened with high strength composites. The three major parts discussed are experimental work, analytical investigations, and a parametric study. Experimental results obtained by other researchers were used to verify the results of the analytical procedures developed. The parametric study provides information on the moment-curvature and load-deflection behavior of strengthened pretensioned prestressed concrete flexural members externally strengthened with fiber-reinforced polymers that can be obtained for various concrete strengths, reinforcement ratios, and varying cross-sections. An analytical model was developed to predict the flexural rigidity of pretensioned, partially prestressed concrete beams that are externally strengthened with high strength composites. CFRP sheets were used for the derivation of equations. The proposed model is based on principles of mechanics and the sectional equations available for the analysis of partially prestressed beams. The model is applicable to the full range of prestressed concrete members covering partially and fully prestressed concrete, straight or harped strands, with or without supplemental mild-reinforcing steel, and varying loading conditions. The procedure can be used to generate the entire load-deflection response and through performing the moment-curvature analysis and estimation of stresses and strains in addition to computing the effective flexural stiffness of the strengthened prestressed member. Comparisons of experimental and analytical results show that deflection can be predicted with good accuracy using the developed modified effective moment of inertia equation. The parametric investigation was conducted on the effect of the basic variables namely, cross-section, concrete compressive strength, prestressing steel ratio, amount of carbon fibers, modulus of elasticity of prestressing steel-to-modulus of elasticity of CFRP ratio, modulus of elasticity of carbon fiber composite, spans, and shear span-to-span ratios. The goal of this investigation was conducted to understand the effect of CFRP strengthening to the flexural stiffness. Rectangular cross-sections with straight bonded prestressing tendons strengthened with 1 to 5 layers of unidirectional carbon sheets were analyzed in the parametric study. Lastly, the application of the proposed effective moment of inertia equation to bonded, pretensioned prestressed members, with harped strands depressed at midspan, externally strengthened with CFRP is examined in comparison with the experimental and analytical response curves.
Keywords: FRP; Prestressed concrete girders; Deflection; Moment-curvature; Fiber reinforced polymers